Problema locuințelor și unele sugestii privind rezolvarea ei - Kivu, Mircea (Calitatea Vieții, 1990)
The study offers a historical survey of the administrative politics, followed by an evaluation of the possibilities of implementing new types of habitat, under the new circumstances manifest in the present development of the Roumanian society.